Turning to the Beginning of the Lithuanian Folksong Publication - Stundžienė, Bronė (Tautosakos darbai, 2018)
Against certain broader context of discussing the historical reflection of relationship between pre-literate culture and writing, the author of the article pays detailed attention to the unusual transformations in folksong development that are brought about by literacy. We usually rightfully consider literacy as an unmistakable indication of cultural progress. In this regard, subsequent recording and printing of folksongs that started in later periods of literacy also merit positive evaluation. Although both modes of fixation belong to the same period of Lithuanian cultural history, however, from the middle of the 18th century until the beginning of the 19th century, printed publications of folksongs acquired immense importance. Looking from a historical distance – the present times, the author of the article reconsiders and reinterprets the sociocultural surroundings of this new mode of folklore dissemination, taking into account what aims the first folklore publishers had and whether or not they managed to achieve them. Essentially, one particular aspect in the beginning of the written Lithuanian folksong tradition is in the focus of attention – namely, how and why the state of folksong altered in the process of becoming a printed source. In the first chapter, following the historical revisions of medieval culture, the author of the article reconsiders the prehistory of folklore publication as the common European process. She takes into account the sociocultural aspects of this period: namely, creations of the “singing peasantry” – the part of the society belonging to the lower classes and engaged in agriculture, which was essentially banned from writing and ignored by the literate society. Like in the rest of Europe, in the medieval literature of the multilingual Grand Duchy of Lithuania and the Lithuanian-speaking Eastern Prussia (currently, the Lithuania Minor), contemporary reflection of folk culture was almost entirely absent or obscure until the middle of the 18th century. As noted in the second chapter, the situation of folk poetry started changing in the Lithuania Minor (the early center of the Lithuanian written culture) with Philip Ruhig publishing his linguistic treatise in 1745 and including (for research purposes) three Lithuanian folksongs. Shortly after, Gotthold Ephraim Lessing reprinted two of them in one of his “Literary Letters” (1759). Subsequently, another famous figure of the German pre-Romanticism and its ideologist Johann Gottfried von Herder included as many as eight Lithuanian folksongs translated into German into his international collection “The Voices of Peoples in Songs”. Thus, the history of Lithuanian folksong publication started with altering attitude towards the so-called “third estate”; this shift is currently regarded as a sociocultural turn inspired by pre-Romanticism and clearing the way for the poetic folk creativity allegedly harboring the “national spirit”. These ideas inspired the famous theologian and pedagogue Liudvikas Rėza (Ludwig Rhesa) to edit the first book of Lithuanian folksongs. This bilingual collection (in Lithuanian and German) saw publication in Konigsberg in 1825. However, traces of the former social separation were persistent. As such, one could name the early tendency of folklore recording and publication: to indicate just the publisher (collector), leaving aside the main actors – the folk singers, although currently they stand out as representatives of the people. Folklorists would subsequently correct this situation. The author of the article goes on to discuss the losses suffered by the folk creativity under the new conditions of literacy. Comparison of the first printed folksongs with their mode of existence in the living folksong process of the 18th – beginning of the 19th century reveals clear changes in the folksong identity. The frozen printed variant loses its capacity to change, along with its former vitality granted by the oral culture; as any other product of the written culture, the printed folksong immediately becomes the past event. Besides, transition from the oral transmission to the area of written culture turns the song into some kind of literary work: therefore, the value of the songs would for a long time since be measured by literary means, and publishing of the songs as poems (leaving out the melodies) would become a common practice. The main thing is, nevertheless, that publication of folksongs in writing and their separate reading completely erase the typical folk communication of ritual culture by means of common places of folksongs – shared for many generations in the pre-literate culture. However, the emerging parallel folksong publication opens up entirely new mode of communication. Already at the very beginning of Lithuanian folksong publication, its publisher obviously acquired individual right to edit the folklore at discretion. Selection of materials for publication (including some changes and reconstructions made along the way) followed primarily the actual purposes of publication, which included presenting the folksong image that would be more readily acceptable to the contemporary readership and satisfy the community’s expectations. It is public knowledge that Rėza, the initiator of the first Lithuanian folksong book, following the nice inspiration of his pre-Romantic period (maintaining that national spirit lived in folklore) also aspired to use folksongs in order to reveal the noble and dignified picture of the ancient Lithuanian people. Part of this picture – harmonious family and correspondingly ideal relations between its members – received vivid attention in this collection. The article concludes with interpretation of a couple of folksongs discussing a case of early insignificant corrections of the motives reflecting the ritual purpose of folksongs. So far, the author leaves aside certain prominent tendencies of re-creation that already have received harsh criticism before.